Common property resources in drylands of India. Issue 6 (18th August 2018) - Gaur, Mahesh Kumar; Goyal, R. K.; Kalappurakkal, S.; Pandey, C. B.
ABSTRACT: Common property resources are areas of land or water being used by a community or a group of communities. These have special significance to peoples and communities who depend on them for their livelihood. The commons in all arid districts of India include village pastures, community forests, wasteland, common threshing grounds, waste dumps, watershed drainage, village baoris 1, talabs 2, nadis 3  and ponds, and tanks, rivers, rivulets, wetlands, riverbeds, community conserved areas, protected areas, Dhaam 4  or Dhooni 5, culturable wastelands, barren & un-culturable land, etc. The area under commons often ranged from 9 to 28% of total village area. Appropriation of the commons by the state for building essential infrastructure such as schools, clinics, veterinary hospitals, housing for government functionaries, SEZ and industrial corridors, etc. is a cause of serious concern. Presently the ownership rights over CPRs are not clear and there are many who claim ownership, some at State level but also like local bodies. The 12 th  plan of the Planning Commission of India recognized and highlighted the need for favourable land tenure arrangements, institutional design and programme architecture in order to achieve effective governance and management of the commons. The revitalization of CPRs is crucial for protecting livelihoods, as well as for biodiversity conservation and for the improvement in arid microclimatic conditions. Dialogue continues on the status of common property resources, the available legal framework and some policy related issues for its conservation through strengthening of local institutions and capacity building for stakeholders.